CFO alert: Do you know what your board audit committee is up to? - GOH, Clarence (Institutional Knowledge at Singapore Management University, 2014)
In October 2014, American Realty Capital Properties – one of the largest real estate investment trusts in the US – stunned the market. Its CEO, David Kay, disclosed that the company had overstated its income in the first quarter of the year – and that executives chose not to correct the error in the second quarter “in order to conceal the error.”